Tropospheric ozone: respiratory effects and Australian air quality goals. Issue 4 (August 1995) - Woodward, A; Guest, C; Steer, K; Harman, A; Scicchitano, R; Pisaniello, D; Calder, I; McMichael, A
Abstract : OBJECTIVE–To review the health effects of tropospheric ozone and discuss the implications for public health policy. DESIGN–Literature review and consultation with scientists in Australia and overseas. Papers in English or with English language abstracts were identified by Medline search from the international peer reviewed published reports. Those from the period 1980-93 were read systematically but selected earlier papers were also considered. Reports on ozone exposures were obtained from environmental agencies in the region. RESULTS–Exposure to ozone at concentrations below the current Australian air quality goal (0.12 ppm averaged over one hour) may cause impaired respiratory function. Inflammatory changes in the small airways and respiratory symptoms result from moderate to heavy exercise in the presence of ozone at levels of 0.08-0.12 ppm. The changes in respiratory function due to ozone are short lived, vary with the duration of exposure, may be modified by levels of other pollutants (such as sulphur dioxide and particulates), and differ appreciably between individuals. Bronchial lavage studies indicate that inflammation and other pathological changes may occur in the airways before reductions in air flow are detectable, and persist after respiratory function has returned to normal. It is not known whether exposures to ozone at low levels (0.08-0.12 ppm) cause lasting damage to the lung or, if such damage does occur, whether it is functionally significant. At present, it is not possible to identify confidently population subgroups with heightened susceptibility to ozone. People with asthma may be more susceptible to the effects of ozone than the general population but the evidence is not consistent. Recent reports suggest that ozone increases airway reactivity on subsequent challenge with allergens and other irritants. Animal studies are consistent with the findings in human populations. CONCLUSION–A new one hour air quality ozone goal of 0.08 ppm for Australia, and the introduction of a four hour goal of 0.06 ppm are recommended on health grounds.